Chiral Brønsted acid-controlled intermolecular asymmetric [2 + 2] photocycloadditions - Evan M. Sherbrook (Nature Portfolio, 2021)
Lewis acids have recently been shown to enable stereocontrol in photochemical cycloadditions, a difficult task due to the reactivity of excited-state compounds. Here the authors show that chiral Brønsted acids are competent chromophore activators in [2+2] cycloadditions, forming diastereomers disfavored in similar Lewis acid catalyzed photochemical reactions.